Globalisation, Knowledge and Lifelong Learning - Jarvis, Peter (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Society?s structures are largely determined by the powerful forces operating at its centre, a place which education has never occupied. But education?s content and functions have always responded to the demands of the centre. However, there has been one notable exception to this in the history of education; adult education has, until very recently, sought to respond to the needs of the people rather than to those of the social system. But in recent years even this form of education, like almost all other forms has been changed and the education of adults and higher education have seemed to be converging as education for employability and for employees continuing to keep abreast in the ever-developing world of commercial knowledge is beginning to dominate the educational scene. Consequently, this paper will examine the way in which knowledge has been appropriated and used in the globalised economy of contemporary society. Finally, it will point to the way that lifelong learning has emerged. It has three parts: the first examines globalisation and the knowledge society, the second the nature of knowledge in the knowledge economy and, thirdly, the processes of lifelong learning.